Quality assessment in Belgian ST elevation myocardial infarction patients: results from the Belgian STEMI database. Issue 6 (2nd November 2018) - Claeys, Marc J.; Sinnaeve, Peter R.; Convens, Carl; Dubois, Philippe; Pourbaix, Suzanne; Vranckx, Pascal; Gevaert, Sofie; De Raedt, Herbert; Beauloye, Christophe; Argacha, Jean-Francois; Evrard, Patrick; Coussement, Patrick
Abstract: The present report describes the quality of care, including in hospital mortality for more than 22.000 STEMI patients admitted in 60 Belgian hospitals for the period 2008–2016. We found a strong increase in the use of primary PCI over time, particularly for patients that were admitted first in a non-PCI capable hospital, reaching a penetration rate of >95%. The transition of thrombolysis to transfer for pPCI in the setting of a STEMI network was, however, associated with an increase of the proportion of patients with prolonged (>120 min) diagnosis-to-balloon time (from 16 to 22%), suggesting still suboptimal interhospital transfer. The in-hospital mortality of the total study population was 6.5%. For non-cardiac arrest patients in-hospital mortality decreased from 5.1% to 3.7%, while it increased for cardiac arrest patients from 29 to 37%. The observation that quality indicators (QI's), such as modalities and timing of reperfusion therapy, were associated with lower levels of mortality, underscores the potential of QIs for STEMI to improve care and reduce unwarranted variation and premature death from STEMI.